2018
DOI: 10.1073/pnas.1713975115
|View full text |Cite
|
Sign up to set email alerts
|

Child first language and adult second language are both tied to general-purpose learning systems

Abstract: Do the mechanisms underlying language in fact serve general-purpose functions that preexist this uniquely human capacity? To address this contentious and empirically challenging issue, we systematically tested the predictions of a well-studied neurocognitive theory of language motivated by evolutionary principles. Multiple metaanalyses were performed to examine predicted links between language and two general-purpose learning systems, declarative and procedural memory. The results tied lexical abilities to lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
119
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 92 publications
(133 citation statements)
references
References 67 publications
9
119
5
Order By: Relevance
“…In regard to the former, the present positive findings are in line with previous research that has attested the role of working memory as an important predictor of L2 learning (e.g., Ando et al 1992;Indrarathne and Kormos, 2018;Juff and Harrington, 2011;Linck et al, 2014;Malone, 2018;Yang et al, 2017). Concerning the latter, the results support the theoretical predictions (Ullman, 2015(Ullman, , 2016 that suggest a role for declarative memory in the acquisition of L2 word knowledge (Buffington and Morgan-Short, 2019;Hamrick et al, 2018;Ullman, 2015Ullman, , 2016Ullman and Lovelett, 2018), but contradict earlier labbased research that found no evidence for such a role (Ruiz et al, 2018). However, the association between declarative memory and lexical learning depended on the kind of test used to measure learners' declarative memory abilities.…”
Section: Research Question 1: Do Working Memory and Declarative Memorsupporting
confidence: 92%
“…In regard to the former, the present positive findings are in line with previous research that has attested the role of working memory as an important predictor of L2 learning (e.g., Ando et al 1992;Indrarathne and Kormos, 2018;Juff and Harrington, 2011;Linck et al, 2014;Malone, 2018;Yang et al, 2017). Concerning the latter, the results support the theoretical predictions (Ullman, 2015(Ullman, , 2016 that suggest a role for declarative memory in the acquisition of L2 word knowledge (Buffington and Morgan-Short, 2019;Hamrick et al, 2018;Ullman, 2015Ullman, , 2016Ullman and Lovelett, 2018), but contradict earlier labbased research that found no evidence for such a role (Ruiz et al, 2018). However, the association between declarative memory and lexical learning depended on the kind of test used to measure learners' declarative memory abilities.…”
Section: Research Question 1: Do Working Memory and Declarative Memorsupporting
confidence: 92%
“…Our results, on the other hand, suggest that difficulties with auditory encoding can be a bottleneck for language acquisition both in childhood and later in life. Thus, some of the mechanisms which facilitate language learning may continue to play similar roles throughout the lifespan (Flege et al, 1999;Birdsong & Molis, 2001;Hamrick, Lum, & Ullman, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the tasks and analyses they employed throw doubt on whether they even assessed the functionality of procedural memory. Procedural memory is operationalized by the PDH as the implicit learning and memory that relies on a network rooted in the basal ganglia (Evans & Ullman, 2016;Hamrick, Lum, & Ullman, 2018;Ullman, 2004Ullman, , 2016Ullman & Pierpont, 2005). Crucially, on this view procedural memory is not isomorphic with implicit learning and memory.…”
Section: Finding #1: Their Me a Sure S Of Procedur Al Le Arning Did Nmentioning
confidence: 99%